Synthesis and bioactivity of 2′, 3′-benzoabscisic acid analogs. Issue 11 (1st June 2015) - Han, Xiaoqiang; Wan, Chuan; Li, Xiuyun; Li, Hong; Yang, Dongyan; Du, Shijie; Xiao, Yumei; Qin, Zhaohai
Graphical abstract: 2′, 3′-Benzoabscisic Acid Analogs with Excellent ABA Like Activity and Preference to Different Physiological Process. Abstract: 2′, 3′-Benzoabscisic acid4a is significantly more active than (±)-ABA and can be potentially used as a plant growth regulator for agriculture. In this study, six4a analogs were designed and synthesized. Bioassay showed that4a displayed greater activity than (±)-ABA and the six analogs produced less inhibition than4a itself. Specially, some analogs displayed markedly different activities to different physiological and biochemical process, which were largely different from ABA and4a . Compared to (±)-ABA, 4b and4c were more effective germination inhibitors for lettuce, but less effective inhibitors for rice elongation. Five-membered analog5 was higher or slightly weaker in inhibiting Arabidopsis seed germination and rice elongation, respectively, but at least 10 times less effective than (±)-ABA in lettuce seed germination. Dual acid6 and alkyne acid20 nearly produced no inhibitory activity for Arabidopsis seed germination, but displayed excellent activity in inhibiting rice seedling growth. The preference of the analogs to different physiology process indicated that they might provide a strategy to develop novel ABA agonists or antagonist and be used as probe to investigate the function of different ABA receptors.